Shifting Cultivation: An ‘Organic Like’ Farming in Nagaland - KUOTSUO, RUKUOSIETUO; CHATTERJEE, DIBYENDU; DEKA, BIDYUT C.; KUMAR, RAKESH; AO, MERASENLA; VIKRAMJEET, KONSAM (Indian Journal of Hill Farming, 2015)
Nâga farmers adopt an age-old traditional cultivation system called shifting cultivation, where a land is selected for cultivation for one or two years and thereafter left it abandoned for several years. About 73% of the people in Nagaland are dependent on agriculture and most of them are involved in shifting cultivation, because of compulsion of its natural hilly topography and traditional way of cultivation. It is a known fact that shifting cultivation has negative impact on soil health and ecosystem. Adopting integrated farming system model may be the best for saving the environment. But, it won’t be possible for someone whose occupation changes drastically overnight. Issuing certificate as ‘organic like’ agriculture to those who wish to practice improved shifting cultivation with minimum impact in theecosystem may alter this environmentally harmful system into less harmful and the poor farmers can fetch a premium price over the conventional products.